Quick Reference Guide to Citrus Insecticides and Miticides - Michael E. Rogers; Philip A. Stansly; Lukasz L. Stelinski; Jamie D. Yates (EDIS, 2009)
Revised! ENY-854, a 2-page illustrated quick reference guide by M.E. Rogers, P.A. Stansly, L.L. Stelinski, and J.D. Yates, lists citrus insecticides and miticides recommended in the Florida Citrus Pest Management Guide, their effects on important citrus pests, and their natural enemies. Published by the UF Department of Entomology and Nematology, August 2008. Revised September 2009.